Primer Design of Sumatran Striped Rabbit (Nesolagus netscheri Schlegel, 1880) using Primer-BLAST and AliView Program - Aurora, Dhea Apriano; Novarino, Wilson; Tjong, Djong Hon; Dahelmi, Dahelmi; Syaifullah, Syaifullah; Setiawan, Arum; Roesma, Dewi Imelda (Jurnal Biologi Tropis, 2025)
The Sumatran striped rabbit (Nesolagus netscheri) lacks specific primers to amplify the chytochrome oxidase 1 (CO1) gene and the chytochrome b (cytb) gene, at present. Therefore, it is important to design primers to amplify the CO1 gene and cytb gene in N. netscheri. The aim of this study is to compare the primer design methods used, namely Primer-BLAST and AliView programs, to design specific primers for the chytochrome oxidase 1 (CO1) and chytochrome b (cytb) genes in N. netscheri. This research was conducted using the descriptive method with molecular observation. In this study, CO1 gene primers, namely [(forward: 5' TGTATGATATGGGGGAGGGC 3'), (reverse: 5' TGGTCCGTCCTTATTACAGCG 3')] and cytochrome b (cytb) gene primers, namely [(forward: CCAGCTCCATCCAATATCTC, (reverse: 5' GTTAGGGTTAGAAGGTCTGC 3')] and showed that primer design using the AliView program produced specific primers in the genus Nesolagus. The conclusion of this study is that primers designed using the AliView program are more specific than those designed using Primer-BLAST.